Empty Streets, Busy Internet: A Time-Series Analysis of Cybercrime and Fraud Trends During COVID-19. (November 2021) - Kemp, Steven; Buil-Gil, David; Moneva, Asier; Miró-Llinares, Fernando; Díaz-Castaño, Nacho
The unprecedented changes in routine activities brought about by COVID-19 and the associated lockdown measures contributed to a reduction in opportunities for predatory crimes in outdoor physical spaces, while people spent more time connected to the internet, and opportunities for cybercrime and fraud increased. This article applies time-series analysis to historical data on cybercrime and fraud reported to Action Fraud in the United Kingdom to examine whether any potential increases are beyond normal crime variability. Furthermore, the discrepancies between fraud types and individual and organizational victims are also analyzed. The results show that while both total cybercrime and total fraud increased beyond predicted levels, the changes in victimization were not homogeneous across fraud types and victims. The implications of these findings on how changes in routine activities during COVID-19 have influenced cybercrime and fraud opportunities are discussed in relation to policy, practice, and academic debate.